THE INFLUENCE OF POPULAR HEALTH TRENDS ON PUBLIC WELL-BEING AND BEHAVIOR - Surrahmi, Surrahmi (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
In recent years, popular health trends have emerged as a significant influence on public health behaviors, shaping both individual lifestyle choices and societal health norms. These trends, driven by social media, celebrity endorsements, and marketing campaigns, have generated widespread awareness about wellness and health issues. However, the impact of such trends on long-term health outcomes remains a topic of debate within the scientific community. This study examines the role of popular health trends, including diet fads, exercise regimes, and mental health practices, in shaping public health behaviors. By analyzing available literature and conducting a survey on public health awareness and behavior, this paper explores how these trends influence attitudes toward well-being and health care choices. The findings suggest that while popular health trends can motivate positive behavior changes, they may also promote unproven or harmful practices. The study highlights the need for a balanced approach in promoting health trends and providing accurate information to the public. Keywords: health trends, public health, wellness, behavior, social media.